Prenylated Flavanones with Anti-tyrosinase Activity from Dalea boliviana - Peralta, Mariana Andrea (2011)
Three new prenylated flavanones, (2S)-5,7,2′-trihydroxy-5′-(1′′′,1′′′-dimethylallyl)-8-prenylflavanone (1), (2S)-5,7,2′-trihydroxy-8,3′-diprenylflavanone (2), and (2S)-5,2′-dihydroxy-6′′,6′′-dimethylchromeno-(7,8:2′′,3′′)-3′-prenylflavanone (3), and a known chromeno (dimethylpyrano) flavanone, obovatin (4), were isolated from the n-hexane extract of Dalea boliviana roots. The compounds were evaluated in vitro in relation to their inhibitory effect on the tyrosinase activity by using a spectrophotometric method.